A further enhancement of the Boyer-Moore-Horspool algorithm applied of LAN chat box profanity filtering - Daryl d. Bonzon and Ronald Harold Giene M. Indol. 4 0 16; 5 (2012)
u
Thesis: (BSCS major in Computer Science) Pamantasan ng Lungsod ng Maynila, 2012.
Keywords: 2 -- 0; 6; 20; 20; 2